Implementation of teaching materials in learning students with intellectual disabilities in english classes - Guillén Jaramillo, Daniela Christel; Tenesaca Morales, Andrés Marcelo (Machala : Universidad Técnica de Machala, 2021)
The main objective of this research is to improve the learning of students with intellectual disabilities in English classes through a system of pedagogical activities using audiovisual materials. Through the review of bibliography, it is argued that audiovisual materials favor the teaching-learning process because they facilitate the comprehension of the contents and the interpretation of the ideas presented. The research is qualitative with a non-experimental design, descriptive and with a case study approach. The instruments used for data collection were observation, interview, pedagogical test, and content analysis was used for data processing. The intervention proposal includes a system of pedagogical activities oriented to students with intellectual disabilities. Finally, it is recommended that future teachers, regardless of their area, make use of pedagogical activities adapted to all types of students, and at the same time that the pedagogical tools favor student learning.
Esta investigación tiene como principal objetivo mejorar el aprendizaje de estudiantes con discapacidad intelectual en las clases de inglés por medio de un sistema de actividades pedagógicas utilizando materiales audiovisuales. A través de la revisión de bibliografía se sostiene que los materiales audiovisuales favorecen al proceso de enseñanza aprendizaje porque facilitan la comprensión de los contenidos y la interpretación de las ideas que se expongan. La investigación es cualitativa con un diseño no experimental, de tipo descriptivo y con un enfoque de estudio de casos. Los instrumentos empleados en la recolección de los datos fueron la observación, entrevista, prueba pedagógica y para el procesamiento de datos se utilizó el análisis de contenidos. La propuesta de intervención abarca un sistema de actividades pedagógicas que está orientada para estudiantes con discapacidad intelectual, Finalmente se recomienda que los futuros docentes independientemente de su área, hagan uso de actividades pedagógicas adaptadas a todo tipo de estudiantes, y a su vez que las herramientas pedagógicas favorezcan el aprendizaje de los estudiantes.
Keywords: TEACHING; LERNING; SYSTEM